Barriers to transition to resource-oriented sanitation in rural Ethiopia - Abebe, Thomas Ayalew; Novotný, Josef; Hasman, Jiří; Mamo, Biruk Getachew; Tucho, Gudina Terefe (Environmental science and pollution research international, 2025)
Recycling excreta resources through resource-oriented toilet systems (ROTS) holds transformative potential, yet adoption remains limited, especially where benefits could be high. This study aims to understand constraints hindering the adoption of ROTS in one such area in Ethiopia. Based on a survey among 476 households comprising 2393 individuals, we examine the plans to use ROTS and willingness to pay for ROTS and apply structural equation modelling to analyze the drivers of these two outcomes while comparing the explanative power of the extended technology acceptance model, extended theory of planned behaviour, and their combined model. While 40% of households expressed a plan to use ROTS and 20% reported willingness to pay for a subsidized ROTS with a biogas unit, merely 7% revealed both the plan to use and sufficient willingness to pay, highlighting the need to target both these complementary outcomes concurrently. The theory of planned behaviour showed the best explanative power, also revealing that these two outcomes are influenced by partly distinct sets of factors. Findings imply that common efforts to ease objective constraints through subsidies, which incentivize willingness to pay, are necessary but not sufficient for facilitating the adoption of ROTS. To simultaneously enhance intentions to use, it is also recommended to target psychosocial drivers, such as perceived behavioural control and perceived community support, through awareness creation, behaviour change activities, and community engagement techniques.
Keywords: Excreta recycling; průzkumy a dotazníky; sanitace; Toilet Facilities; toalety; recyklace; Surveys and Questionnaires; lidé; Willingness to pay; venkovské obyvatelstvo; Recycling; Ethiopia; Eco-toilet; Etiopie; Resource-oriented sanitation; Resource recovery; Rural Population; Sanitation; Humans